Mitochondrial Homeostasis and Signaling in Parkinson’s Disease - Scorziello, Antonella; Borzacchiello, Domenica; Sisalli, Maria Jose; Di Martino, Rossana; Morelli, Micaela; Feliciello, Antonio (Frontiers in Aging Neuroscience, 2020)
The loss of dopaminergic (DA) neurons in the substantia nigra leads to a progressive, long-term decline of movement and other non-motor deficits. The symptoms of Parkinson’s disease (PD) often appear later in the course of the disease, when most of the functional dopaminergic neurons have been lost. The late onset of the disease, the severity of the illness, and its impact on the global health system demand earlier diagnosis and better targeted therapy. PD etiology and pathogenesis are largely unknown. There are mutations in genes that have been linked to PD and, from these complex phenotypes, mitochondrial dysfunction emerged as central in the pathogenesis and evolution of PD. In fact, several PD-associated genes negatively impact on mitochondria physiology, supporting the notion that dysregulation of mitochondrial signaling and homeostasis is pathogenically relevant. Derangement of mitochondrial homeostatic controls can lead to oxidative stress and neuronal cell death. Restoring deranged signaling cascades to and from mitochondria in PD neurons may then represent a viable opportunity to reset energy metabolism and delay the death of dopaminergic neurons. Here, we will highlight the relevance of dysfunctional mitochondrial homeostasis and signaling in PD, the molecular mechanisms involved, and potential therapeutic approaches to restore mitochondrial activities in damaged neurons.